2019
DOI: 10.1111/sjop.12590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cognitive behavioural therapy and return‐to‐work intervention for patients on sick leave due to stress‐related disorders: Results from a randomized trial

Abstract: The aim of this study was to evaluate specific effects for patients with adjustment or exhaustion disorder, the Stress subgroup (n = 152), regarding symptom severity and sick leave after CBT, a return‐to‐work intervention (RTW‐I), and a combination of them (COMBO), using data from a randomized trial. In the original study, primary care patients on sick leave (N = 211) were randomized to CBT (n = 64), RTW‐I (n = 67), or COMBO (n = 80). Blinded Clinician Severity Rating (CSR) of symptoms and sick leave registry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 42 publications
(56 reference statements)
0
38
0
Order By: Relevance
“…A recent meta-analysis (13) suggests that work-directed interventions (occupational therapy and multi-component work intervention incorporating work modification and support) combined with a clinical intervention can be effective in reducing sickness absence and that enhancing occupational or primary care with CBT and structured telephone outreach with care management that includes medication has the potential to reduce sick leave; however, the number of related studies is small. Salomonsson et al (14) performed a randomized trial that compared the effects of CBT, RTW intervention, and a combination of them (COMBO) on a stress subgroup (n = 152 with adjustment disorder or exhaustion disorder) and DepAnxIn subgroup (n = 59 with depression, anxiety disorders, or insomnia). The stress subgroup showed a superior reduction of stress-related symptoms after CBT compared to RTW intervention, but there was no significant difference between the COMBO and RTW intervention or CBT.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis (13) suggests that work-directed interventions (occupational therapy and multi-component work intervention incorporating work modification and support) combined with a clinical intervention can be effective in reducing sickness absence and that enhancing occupational or primary care with CBT and structured telephone outreach with care management that includes medication has the potential to reduce sick leave; however, the number of related studies is small. Salomonsson et al (14) performed a randomized trial that compared the effects of CBT, RTW intervention, and a combination of them (COMBO) on a stress subgroup (n = 152 with adjustment disorder or exhaustion disorder) and DepAnxIn subgroup (n = 59 with depression, anxiety disorders, or insomnia). The stress subgroup showed a superior reduction of stress-related symptoms after CBT compared to RTW intervention, but there was no significant difference between the COMBO and RTW intervention or CBT.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these focus on psychological symptoms, e.g. [16] in order to reduce stress, but have so far only generated marginal outcomes [17]. There is not only a need for treatments for reducing psychological symptoms, but also for health promotion interventions for enabling individuals to improve their health and well-being [18].…”
Section: Introductionmentioning
confidence: 99%
“…Some trials found minute effects [6,7] and in one case even a trend to worsen the problems [8]. In contrast, the use of cognitive behavioral therapy (CBT) has accomplished increased well-being of individual patients presenting with psychosocial problems and psychologists now systematically apply CBT in many primary health care centers in Sweden [5,6,9]. However, when focusing on the effects of CBT treatment of patients to reduce sick leave, the trials give a more controversial impression.…”
Section: Introductionmentioning
confidence: 99%